APLIKASI PELAYANAN SERVICE SEPEDA MOTOR - Indra Maulana Yusup Kusumah; Mochammad Syaiful; Herna Gunawan (LPPM STMIK BANDUNG, 2016)
The addition of motor vehicle population is increasing every year, for it was the same vehicle used should always be in good condition. Needs service for motorcycles into a routine needs to be done by the user. Therefore it takes an application support service motorcycle service to customers. The method used in the service motorcycle service is Prototype method where data collection techniques that are used, among others, interviews and observations. The design method in this design step will be described by use case diagrams, activity diagrams, sequence diagrams, class diagrams. The software used is PHP, MySQL, phpMyAdmin.From the results of this study, researchers will design an application that can process data service motorcycle service which is expected to facilitate and improve services. Keywords: Motorcycle repair, service online, the website application.